Analisis Wacana Kritis Model Teun Van Dijk pada Kanal Youtube Ferry Irwandi Yang Berjudul “Salah Respon Pemerintah Soal Tiktok” - Abimanyu, Giovanni Dimas (Crises on Languages and Literature, 2024)
The issue of e-commerce Tiktok Shop has been widely discussed lately due to the assumption that e-commerce Tiktok Shop is considered to violate regulations and is detrimental to society. This resulted in the government's repressive response, which immediately closed Tiktok Shop and prohibited it from operating. The main object of this study is a YouTube video from a channel named Ferry Irwandi. Ferry Irwandi's YouTube channel, precisely in the video content entitled "The Government's Wrong Response to Tiktok," discusses the government's misconceptions, packaged in a good narrative from Ferry Irwandi. The data in this study are in the form of statements made by Ferry Irwandi throughout the video.